PROBLEMATIKA GURU PENDIDIKAN AGAMA ISLAM DALAM PERENCANAAN PEMBELAJARAN KELAS INKLUSI - Ahmad Syaddad; Nur Fadillah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
The demand for PAI teachers who have special backgrounds in teaching inclusive students is increasing, but their availability is minimal. In education, addressing the needs of inclusive students is urgent and complex. The purpose of this study is to dig deeper into the problems faced by PAI teachers in the inclusion class at SDN 003 Tanjung Redeb. The research method used was qualitative, the subjects of this study were Waka Curriculum and PAI Teachers who taught Inclusion classes at SDN 003 Tanjung Redeb, The data collection methods used were documentation and interviews. The data analysis used in this study is non-statistical, which uses qualitative descriptive analysis. The results showed that the problems in planning inclusive learning at SDN 003 Tanjung Redeb, Berau Regency, were related to PAI teacher educators and ABK students. The problem is also caused by the lack of attention of the Berau District Education Office and the full support of relevant schools that carry out inclusion classes. This includes the ability of PAI teachers to plan effective learning and develop learning media that suits their needs.